Building resilient start-up: a comprehensive strategic framework for start-up survival - Ibrahim, Irme Rafhan; Mustafa, Ammar Yasir; Hanif, Aqilah; Hamdan, Batrisyia Tihani; Ruslan, Maisarah; Wan Yusoff, Wan Hafiz Aizuddin; Ramli, Suriana (Universiti Teknologi MARA, Kedah, 2023)
Start-ups are an essential aspect of the Malaysian economy, as they have the ability to generate economic growth and competitiveness. Malaysian start-ups have numerous challenges regarding funding, market information, and sustainability. The difficulties may cause the start-up to be unable to continue operations. A comprehensive framework includes effective funding mechanisms, market intelligence availability, and establishing a sustainable start-up model. Potential solutions have been proposed for each component, including improved communication and collaboration between start-ups and funding institutions. Centralized databases and mentorship programs can assist start-ups in identifying funding opportunities and mentors to help them navigate the application process. Improving market intelligence entails providing start-ups with the knowledge, skills, exposure, and experience needed for effective market research. Incubator and accelerator programs can assist start-ups in developing market information, entrepreneurship skills, and network building. Creating a sustainable company strategy entails putting social and environmental responsibilities first. Start-ups can develop products or services that solve specific social or environmental requirements, use environmentally friendly materials and reduce waste. Economic benefits, better entrepreneurship skills, and entrepreneur sustainability towards a successful start-up are all expected outcomes of following this strategic framework. Start-ups have the potential to establish a positive reputation, attract loyal customers, and contribute to a more sustainable future for all. Malaysia's start-up ecosystem has immense potential, and start-ups can continue to develop and prosper, given the correct support and resources. Malaysia can construct a solid and vibrant start-up ecosystem, promote economic growth and competitiveness, attract investment, generate jobs, and, most importantly, ensure the start-up's survival. However, more work has to be done to tackle the sustainability problems that start-ups face and fully realize their promise of moving Malaysia's economy ahead.